Weight Change 2 Years After Termination of the Intensive Lifestyle Intervention in the Look AHEAD Study. Issue 5 (22nd April 2020) - ; Chao, Ariana M.; Wadden, Thomas A.; Berkowitz, Robert I.; Blackburn, George; Bolin, Paula; Clark, Jeanne M.; Coday, Mace; Curtis, Jeffrey M.; Delahanty, Linda M.; Dutton, Gareth R.; Evans, Mary; et al.
Abstract : Objective: This study evaluated weight changes after cessation of the 10‐year intensive lifestyle intervention (ILI) in the Look AHEAD (Action for Health in Diabetes) study. It was hypothesized that ILI participants would be more likely to gain weight during the 2‐year observational period following termination of weight‐loss–maintenance counseling than would participants in the diabetes support and education (DSE) control group. Methods: Look AHEAD was a randomized controlled trial that compared the effects of ILI and DSE on cardiovascular morbidity and mortality in participants with overweight/obesity and type 2 diabetes. Look AHEAD was converted to an observational study in September 2012. Results: Two years after the end of the intervention (EOI), ILI and DSE participants lost a mean  (SE) of 1.2  (0.2) kg and 1.8  (0.2) kg, respectively ( P  = 0.003). In addition, 31% of ILI and 23.9% of DSE participants gained ≥ 2% ( P  < 0.001) of EOI weight, whereas 36.3% and 45.9% of the respective groups lost ≥ 2% of EOI weight ( P  = 0.001). Two years after the EOI, ILI participants reported greater use of weight‐control behaviors than DSE participants. Conclusions: Both groups lost weight during the 2‐year follow‐up period, but more ILI than DSE participants gained ≥ 2% of EOI weight. Further understanding is needed of factors that affected long‐term weight change in both groups.